Irreversible Thermodynamics and Bioeconomy: Toward a Human-Oriented Sustainability - Lucia, Umberto; Grisolia, Giulia (Frontiers in Physics, 2021)
The present age is characterized by a very complex economic relationship among finance, technology, social needs, etc., which can be summarised in the word `sustainability'. The sustainable consumption and production policies represent the keys to realise sustainable development. But, the analysis of the carbon footprint data points out that the present economies are still carbon-consumption production. The reduction of greenhouse gasses emissions is based on a shift from fossil to renewable and bio-based industrial raw materials, with a related reorganization of the chains of the energy and manufacturing sectors. But, this requirement implies technological choices, based on a sustainable measurement of their impacts on the ecological and economical contexts. So, social and economic requirements must also be taken into account by the decision-makers. Bioeconomy can represent a possible approach to deal with the requirements of the present time. But, new needs emerge in relation to sustainability. So, sustainable policies require new indicators, in order to consider the link among economics, technologies, and social well-being. In this paper, an irreversible thermodynamic approach is developed, in order to introduce a thermoeconomic indicator, based on thermodynamic optimisation methods, but also on socio-economic and ecological evaluations. The entropy production rate is introduced in relation to the CO_2 emission flows from human activities, and it is related to the Income Index, in order to consider the economic and social equity. This approach is of interest of the researchers in the field of econophysics, thermoeconomy, economics and bioeconomy.